Effect of Quxie capsule in patients with colorectal cancer: A systematic review and meta-analysis. Issue 7 (19th February 2021) - Zhang, Suqin; Lian, Peng; Huang, Tao; Zhou, Jianhua
Abstract: Objective: To investigate whether the Quxie capsule can decrease relapse, metastasis, and symptoms, as well as alleviate the side effects in colorectal cancer (CRC) patients. Methods: A comprehensive literature search of multiple databases was performed. Two reviewers independently selected trials that assessed the relapse-metastasis rate, degree of symptoms, and side effects of Quxie capsule for CRC. The meta-analysis was performed using Review Manager 5.3. Results: This meta-analysis included 6 studies, with a total of 408 cases. The quality of the included studies was generally low, with only 1 trial of high quality. A statistically significant difference was observed in the relapse-metastasis rate between the Quxie capsule and control groups after 2-years follow-up (n = 185, relative risk (RR) = 0.13, 95% confidence interval (CI) 0.04–0.46; P = .002). The Quxie capsule was found to reduce the traditional Chinese medicine symptom score as compared to the control (n = 208, weighted mean differences (WMD) = −4.15, 95% CI −7.30 to −1.00; P = .010), while it showed no significant improvement in the Karnofsky Performance Status score (n = 138, WMD = 5.05; 95% CI −2.95 to 13.04; P = .22). There was no difference in adverse events between the 2 groups ( P = .66). Conclusion: This systematic review and meta-analysis showed no clear superiority of Quxie capsule for CRC patients receiving chemotherapy. The effect of Quxie capsule in CRC patients should be examined by high quality, large sample size, multi-center RCTs, with longer follow-up.